Knowledge, attitude and practice of blood donation among undergraduate students in a public university, Malaysia - Japar, S.; Yahya, N.A.; Raman, R.A.; Sani, A.M.; Halain, Azura; Geok, K.I.M.; Soh, K.L.S. (2018)
Blood donation save millions of lives. An increasing demand for blood in almost all medical centers throughout Malaysia indicated the requirement for more blood donors. The current strategy of blood donor programs in all blood centers in order to overcome the shortage of donations of safe blood in Malaysia is to make a maximum effort to recruit safe blood donors from special, low-risk groups, such as university students. The study was to determine the knowledge, attitude, and practices among undergraduate health sciences students regarding blood donations in a public university. A cross-sectional study was conducted among undergraduate health sciences students. The data were collected from February until April 2016 and SPSS, version 20.0 was used to analyze the data. The result revealed, a total of 210 undergraduate health sciences student participated in this study. Approximately, 46.2% had adequate knowledge, 57.1% had a positive attitude towards blood donation and less than 50% of the respondents had ever donated blood. Although there is positive attitude of blood donation among student but there is low level of knowledge of blood donation. Therefore, there is need to intensify public awareness and knowledge on blood donation. The campaign on blood donation should be continued with various methods to create more opportunities for the students, which can greatly enhance their knowledge, promote positive attitude and good blood donation practice.